Experimental and Computer Research of Reinforced Concrete Columns Under High Temperature Effects - Surianinov, M.G.; Otrosh, Yu.A.; Balduk, P.G.; Dadashov, I.F. (Science and Innovation, 2024)
Introduction. The unsatisfactory technical condition of many buildings and structures is the result of their aging and requires a quick evaluation of the technical condition. Problem Statement. It is necessary to conduct an experimental research, since it is analytically difficult to describe the stress-strain state of structures. The most promising way for verifying these experimental research data is computer simulation of structures, including in the condition of a fire. It is advisable to use the ANSYS software. Purpose. To carry out experimental studies of the stress-strain state of a reinforced concrete column at a high temperature and to make a computer simulation of the process with subsequent comparison of the results. Materials and Methods. Experimental fire tests of reinforced concrete columns have been conducted in order to determine the time interval between the start of the test and the establishment of normalized limit of fire resistance for the column based on the loss of bearing capacity in the conditions of normal temperature conditions. In order to evaluate the quality of the experiment and the reliability of the obtained temperature distribution, a computer simulation of the two columns using the ANSYS R.17.1 software has been made. Results. A comparative analysis of the results of experimental studies and a numerical analysis have been done. The temperature field distribution in the column is ambiguous and depends on the location of control points. Conclusions. The obtained results have confirmed that the experimental research and computer simulation with further numerical analysis can be recommended for practical use. The mathematical model makes it possible to operatively predict the controlled parameters of building structures. Conclusions on the operability of building structures with the possible tendency to deterioration of their technical condition under force impact and high temperature effects taken into consideration are advisory rather than mandatory.